(untitled) - Nguyen Thi Le Vinh, Dinh Trung Thanh, Vu Thi Phuong Le, Nguyen Phan Thu Hang, Ton Nu Hai Yen (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The paper identifies the challenges and opportunities of security, economy, governance methods, and external relations that the Trump administration’s Indo-Pacific Free and Open Strategy brings to Vietnam through the analysis of implementation of this strategy published in official US government documents and research papers; through the synthesisand statistics of data related to Vietnam-US relations in the past 10 years; through a comparison of the pillars of the strategy to the national interests of Vietnam.The concept of the Indian Ocean-Pacific Ocean region is not new in the geopolitical strategy calculations of the powers for Asia. But this concept was only really noticeable in recent times when President Donald Trump spoke about America’s vision of the Indian-Pacific strategy for the first time at the Asia-Pacific Economic Cooperation (APEC) Summit held in Da Nang, Vietnam in November 2017. Vietnam is particularly interested in how this strategy will be implemented to shape its security environment. From the identification of the challenges and opportunities that the strategy brings to Vietnam, we suggest a number of measures for Vietnam’s leaders to make policies to improve the effectiveness of foreign affairs in a new context.